Topographic-anatomical Relationships of the Arterial and Venous Beds of the Kidneys - Sh. I. Akbaev; Z. U. Lechiev; E. S. Kafarov (Здоровье мегаполиса, 2025)
Background. Anatomical and topographic features of the arterial and venous bed of the kidneys are crucial for the proper functioning of the organ and affect the onset of various pathologies, such as hypertension, chronic kidney disease, venous thrombosis, and venous congestion. The kidneys have a complex vascular system, including the renal artery, which supplies the organ with blood, and the renal vein, which ensures blood outflow. Disturbances in these anatomical structures can lead to significant clinical consequences.Purpose. The article analyzes the topographic and anatomical features of the vascular structures of the kidneys and their relationships. It examines the primary mechanisms that may lead to pathologies associated with impaired blood circulation in the kidneys. In particular, the discussion focuses on the pathophysiology of arterial hypertension, which often occurs due to impaired microcirculation in the kidneys, and chronic kidney disease (CKD), including their vascular aspects. The article also examines modern diagnostic methods such as angiography, ultrasound diagnostics, and MRI, which allow detecting changes in the arterial and venous bed of the kidneys at early stages. Issues associated with impaired venous outflow of blood from the kidneys can cause the development of chronic renal failure, which requires timely diagnosis and intervention.Conclusions. The author of the article emphasizes the importance of early detection of vascular disorders of the kidneys and the development of effective preventive programs aimed at reducing morbidity and mortality associated with kidney disease. Measures that can be introduced into the public health system are discussed, such as regular screening programs for patients at risk of developing vascular diseases, as well as training programs for health workers.